Promoting economic and social development through an innovative investment framework: the multidimensional role os ACFIs - Beatriz F Campos Nóbrega (International Journal of Digital Law)
The economic performance of a country, in the era of a globalized economy and its value chains, is strongly affected by foreign investments. The regulation of this cross-border capital flow through international instruments negotiated and celebrated to facilitate, boost and protect foreign investments demonstrates the potential of these instruments in shaping a responsible and diligent insertion of foreign investments in the host country. In Brazil, the investment agreements have been, in the recent years, negotiated through the so-called Cooperation and Facilitation Investment Agreements (CFIAs). So why not use this important mechanism to build a more efficient system? It urges that International Investment Law is brought into this debate, leading the way to incorporating socially responsible corporate conducts into the productive economic process by both States and investing economic agents. This study seeks, therefore, to evaluate Responsible Business Conduct in its interrelation with investment mechanisms that can, at once, attract and facilitate investment and also promote economic and social development.